(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Education is an important factor in determining theentrepreneurial orientation in individuals. Formal education is positivelycorrelated with entrepreneurship. Education and training can have definite rolein enhancing entrepreneurship in the context of a developing country like Indiaby enlarging the pool of entrepreneurs. Unfortunately, the presententrepreneurship education in India just concentrates on related courses.Moreover, the so called entrepreneurship courses are similar to the generalbusiness courses. But general business management education has no significant influenceon entrepreneurial propensity. There is a demand for education programsspecifically designed to expand students’ knowledge and experience inentrepreneurship. This paper attempts to explain the evolution ofentrepreneurship education in India, and discuss the importance ofentrepreneurship education. It further discusses the challenges faced byentrepreneurship. and suggestion for developing the entrepreneurship education.